2000
DOI: 10.1626/pps.3.140
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Wheat and Maize Roots as Influenced by Biopores in a Subsoil of the Kanto Loam Type

Abstract: : Biopores are tubular soil macropores left by plant roots after their decay or burrowed by soil animals, which provide channels for deep rooting and improve crop access to water and nutrients. The density of biopores, number of biopores per unit area, and proportion of biopores occupied by roots were measured on horizontal soil profiles at 30, 50, and 70 em in depth in a fine-texture subsoil of Andosol (Light clay, a volcanic ash of the Kanto loam type) at the mature stage of wheat and maize. Images of 0. 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…The mean share of subsoil RLD in biopores relative to total subsoil RLD observed in the field experiment amounted to 10% on the last day of measurement, which is rather low compared with values from the literature, where shares of 14 to 100% have been reported (Ehlers et al, 1983; Gaiser et al, 2013; Nakamoto, 2000; White and Kirkegaard, 2010). The reasons for this large variability in biopore RLD observed in different studies are manifold and include crop species, soil structure and texture, but above all diverging definitions of biopores with regard to diameter as well as different methods to assess the root distribution within the bulk soil and biopores (e.g., profile wall method, Böhm and Koepke, 1977; core‐break method, Kirkegaard et al, 2007).…”
Section: Discussioncontrasting
confidence: 75%
“…The mean share of subsoil RLD in biopores relative to total subsoil RLD observed in the field experiment amounted to 10% on the last day of measurement, which is rather low compared with values from the literature, where shares of 14 to 100% have been reported (Ehlers et al, 1983; Gaiser et al, 2013; Nakamoto, 2000; White and Kirkegaard, 2010). The reasons for this large variability in biopore RLD observed in different studies are manifold and include crop species, soil structure and texture, but above all diverging definitions of biopores with regard to diameter as well as different methods to assess the root distribution within the bulk soil and biopores (e.g., profile wall method, Böhm and Koepke, 1977; core‐break method, Kirkegaard et al, 2007).…”
Section: Discussioncontrasting
confidence: 75%
“…Nakamoto (2000) found that there is a higher proportion of roots growth in wheat than in corn through compacted soil layers. It is mainly because they have a smaller diameter in relation to the biopore diameter, allowing an easily change of direction when they meet each other, and enabling a greater ability of breaking higher density soils.…”
Section: Effect Of Soil Density To Rootmentioning
confidence: 97%
“…1d). The difference at 10-40 cm depth might be related to root distribution and maize/wheat rotation because the root distribution of vegetables is much more restricted than that of maize or wheat (Zotarelli et al, 2009;Nakamoto, 2000). (Fig.…”
Section: Soc Ic and Tnmentioning
confidence: 99%